Natural Biflavonoids Modulate Macrophage–Oxidized LDL Interaction In Vitro and Promote Atheroprotection In Vivo - Tabares-Guevara, Jorge H.; Lara-Guzmán, Oscar J.; Londoño-Londoño, Julian A.; Sierra, Jelver A.; León-Varela, Yudy M.; Álvarez-Quintero, Rafael M.; Osorio, Edison J.; Ramirez-Pineda, José R. (Frontiers in Immunology, 2017)
The accumulation of oxidized ApoB-100-containing lipoproteins in the vascular intima and its subsequent recognition by macrophages results in foam cell formation and inflammation, key events during atherosclerosis development. Agents targeting this process are considered potencially atheroprotective. Since natural biflavonoids exert antioxidant and anti-inflammatory effects, we evaluated the atheroprotective effect of biflavonoids obtained from the tropical fruit tree Garcinia madruno. To this end, the pure biflavonoid aglycones Morelloflavone and Volkensiflavone, as well as the Morelloflavone’s glicoside Fukugiside were tested in vitro in primary macrophages, whereas a biflavonoid fraction with defined composition (85% Morelloflavone, 10% Volkensiflavone, 5% Amentoflavone) was tested in vitro and in vivo. All biflavonoid preparations were potent ROS scavengers in the ORAC assay, and most importantly, protected LDL particle from both lipid and protein oxidation. In biflavonoid-treated macrophages, the surface expression of the oxLDL receptor CD36 was signifcantly lower than in vehicle-treated macrophages. Uptake of fluorescently-labelled oxLDL and cholesterol accumulation were also attenuated in biflavonoid-treated macrophages and followed a pattern that paralleled that of CD36 surface expression. Fukugiside and Volkensiflavona inhibited oxLDL-induced ROS production and IL-6 secretion, respectively, whereas all aglycones, but not the glucoside Fukugiside, inhibited the secretion of one or more of the cytokines IL-1β, IL-12p70, and MCP-1 in LPS-stimulated macrophages. Interestingly, in macrophages primed with low-dose LPS and stimulated with cholesterol crystals, IL-1β secretion was significantly and comparably inhibited by all biflavonoid preparations. Intraperitoneal administration of the defined biflavonoid fraction into ApoE-/-mice was atheroprotective, as evidenced by the reduction of the atheromatous lesion size and the density of T cells and macrophages infiltrating the aortic root; moreover, this treatment also lowered the circulating levels of cholesterol and the lipid peroxidation product malondialdehyde. These results reveal the potent atheroprotective effects exerted by biflavonoids on key events of the oxLDL-macrophage interphase: i) atheroligand formation, ii) atheroreceptor expression, iii) foam cell transformation, and iv) pro-oxidant/proinflammatory macrophage response. Furthermore, our results also evidence the antioxidant, anti-inflammatory, hypolipemiant and atheroprotective effects of Garcinia madruno’s biflavonoids in vivo.